Preparation of suspensions of phospholipid-coated microbubbles by coaxial electrohydrodynamic atomization. - Farook, U; Stride, E; Edirisinghe, M (2009)
The use of phospholipid-coated microbubbles for medical applications is gaining considerable attention. However, the preparation of lipid-coated microbubble suspensions containing the ideal size and size distribution of bubbles still represents a considerable challenge. The most commonly used preparation methods of sonication and mechanical agitation result in the generation of polydisperse microbubbles with diameters ranging from less than 1 microm to greater than 50 microm. Efforts have been made via distinctly different techniques such as microfluidic and electrohydrodynamic bubbling to prepare lipid-coated microbubbles with diameters less than 10 microm and with a narrow size distribution, and recent results have been highly promising. In this paper, we describe a detailed investigation of the latter method that essentially combines liquid and air flow, and an applied electric field to generate microbubbles. A parametric plot was constructed between the air flow rate (Qg) and the lipid suspension flow rate (Ql) to identify suitable flow rate regimes for the preparation of phospholipid-coated microbubbles with a mean diameter of 6.6 microm and a standard deviation of 2.5 microm. The parametric plot has also helped in developing a scaling equation between the bubble diameter and the ratio Qg/Ql. At ambient temperature (22 degrees C), these bubbles were very stable with their size remaining almost unchanged for 160 min. The influence of higher temperatures such as the human body temperature (37 degrees C) on the size and stability of the microbubbles was also explored. It was found that the mean bubble diameter fell rapidly to begin with but then stabilized at 1-2 microm after 20 min.